INCOME INEQUALITY IN TRANSITION ECONOMIES: A COMPARATIVE ANALYSIS OF CROATIA, SERBIA AND SLOVENIA - Žarković Rakić, Jelena; Krstić, Gorana; Oruč, Nermin; Bartlett, Will (Economic Annals, 2019)
This paper investigates the relationship between income inequal-ity and different welfare state trajectories that three countries of the former Yugo-slavia “south of the Alps” have taken over the three decades since the breakup of the country in 1990. It is remarkable that three countries emerging from a common (social-ist) system have experienced diametrically opposing outcomes regarding inequality. Slovenia has one of the lowest levels of in-come inequality in Europe, Croatia an av-erage level of inequality, and Serbia one of the highest levels. The paper first examines the extent and nature of income inequality in the three countries before examining the determining causes of inequality, rooted in the evaluation of labour markets, edu-cation systems, and tax-benefit systems. It concludes that the divergent transition paths have created the different inequality outcomes observed in the three countries.